2015
DOI: 10.1039/c5fo00669d
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate extract induces ellagitannin metabolite formation and changes stool microbiota in healthy volunteers

Abstract: The health benefits of pomegranate (POM) consumption are attributed to ellagitannins and their metabolites, formed and absorbed in the intestine by the microbiota. In this study twenty healthy participants consumed 1000 mg of POM extract daily for four weeks. Based on urinary and fecal content of the POM metabolite urolithin A (UA), we observed three distinct groups: (1) individuals with no baseline UA presence but induction of UA formation by POM extract consumption (n = 9); (2) baseline UA formation which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(97 citation statements)
references
References 39 publications
2
92
0
3
Order By: Relevance
“…Specifically, dietary supplementation of cranberry extract and Concord grape polyphenols increased A. muciniphila abundance in feces from 2% to over 30% (OTU sequences) and from 6.2% to 49.1% on the high-fat fed DIO mice, respectively (Anhê et al, 2015; Roopchand et al, 2015). Whereas the intake of pomegranate extract, green tea extract, and whole California table grape showed no effect on A. muciniphila abundance of healthy humans or DIO mice (Axling et al, 2012; Baldwin et al, 2016; Li et al, 2015). The inconsistent results suggest that the A. muciniphila -promoting effects of dietary polyphenols are highly depended on their chemical nature and sources.…”
Section: Evidence From Dietary Polyphenol: Inconsistent Results Frmentioning
confidence: 89%
See 1 more Smart Citation
“…Specifically, dietary supplementation of cranberry extract and Concord grape polyphenols increased A. muciniphila abundance in feces from 2% to over 30% (OTU sequences) and from 6.2% to 49.1% on the high-fat fed DIO mice, respectively (Anhê et al, 2015; Roopchand et al, 2015). Whereas the intake of pomegranate extract, green tea extract, and whole California table grape showed no effect on A. muciniphila abundance of healthy humans or DIO mice (Axling et al, 2012; Baldwin et al, 2016; Li et al, 2015). The inconsistent results suggest that the A. muciniphila -promoting effects of dietary polyphenols are highly depended on their chemical nature and sources.…”
Section: Evidence From Dietary Polyphenol: Inconsistent Results Frmentioning
confidence: 89%
“…Also, in the human study, although pomegranate extract did not change A. muciniphila abundance in the feces, the bacterium was 33-fold and 47-fold higher in stool samples of the subjects who are able to produce pomegranate metabolite urolithin as compared to non-producers at baseline and after 4 weeks dietary treatment, respectively. This suggested that A. muciniphila might play an important role in the breakdown of phenolic compounds in the intestine and specific group of humans may benefit more from polyphenols for promoting A. muciniphila (Li et al, 2015). In summary, since dietary polyphenols are so diverse and abundant, a validated in vitro SHIME model would be very helpful as a quick tool to screen and detect which polyphenols are effective in promoting A. muciniphila growth, then animal and human studies could be followed up for verifying their activities.…”
Section: Evidence From Dietary Polyphenol: Inconsistent Results Frmentioning
confidence: 99%
“…and Thermovenabulum spp. [115]. It was noted that urolithin producers hosted at zero time a 33-fold greater population of Akkermansia muciniphila (phylum Actinobacteria) than the non-producers, and that after supplementation this differential was 47-fold [115], whereas Romo-Vaquero et al were able to associate urolithin A production with Gordonibacter [116], an organism not detected by Li et al These studies clearly demonstrate that there are two metabotypes with regard to ellagitannin catabolism -one for whom urolithin production is easily inducible and the other for which induction by dietary supplementation is more difficult or impossible, and that certain transformations can be achieved by more than one genus.…”
Section: Prebiotic Effectsmentioning
confidence: 99%
“…Flavonols [57], quercetin [58,59], catechin and puerarin [59], anthocyanins [47], ellagitannins [60], resveratrol [61] and trans-resveratrol [58] are all reported to impact the activities of the GM. Quercetin supplementation resulted in an altered composition of the GM at different taxonomic levels, including the FBR and inhibiting the growth of bacterial species associated with diet-induced obesity, such as Erysipelotrichaceae, Bacillus spp., and Eubacterium cylindroides [58].…”
Section: Effect Of Minor Food Compounds On the Human Gut Microbiotamentioning
confidence: 99%
“…significantly. Li et al [60] demonstrated that ellagitannins can stimulate the growth of several bacterial genera with beneficial properties for human health, such as Akkermansia muciniphila, Butyrivibrio, Escherichia, Lactobacillus or Prevotella. Proanthocyanidins from grape seed can increase Lachnospiraceae, Clostridiales, Lactobacillus and Ruminococcacceae in female pigs [63].…”
Section: Effect Of Minor Food Compounds On the Human Gut Microbiotamentioning
confidence: 99%